Stability Analysis of Retaining Soil Walls Protecting Banu Canal, Ngantru Village, Ngantang District, Malang-Indonesia - Suhudi Suhudi; Fifi Damayanti (Journal of Evrímata: Engineering and Physics, 2024)
The frequent occurrence of landslides in the Ngantang District, Malang Regency, especially in Ngantru Village, is caused by topographic conditions, where the area is hilly because it is located at the foot of Mount Kelud. Likewise, along the Banu Irrigation Area Channel there are points prone to landslides, especially in the upstream part. These landslides result in the channel breaking so that the irrigation water supply is disrupted. DPT (Soil Retaining Wall) is a building structure whose role is to maintain the stability of the soil on sloping land. The existence of this wall is expected to be able to prevent the soil from moving or landslides. Therefore, to protect the Banu Irrigation Area Channel, a DPT construction was built where the DPT details used were stone masonry construction or the Gravity Wall type. With a total height of 3.9 m, the bottom sole width is 1.00 m and the upper sole width is 0.50 m. The purpose of this paper is to analyze whether the existing DPT is safe  against the forces that work, especially analyzing its stability, then comparing it with other DPT designs with the Cantilever Wall type. Based on the analysis of calculations for the Existing Gravity Type Earth Retaining Wall, the stability figures for soil bearing capacity σ max= 23.76 > 15.012 (safe ), stability against sliding hazards Fgs=3.321 ≥ 1.5 (safe ), and stability against sliding hazards Fgs=3.321 ≥ 1.5 (safe ) are obtained. = 6.26 > 1.5 (safe ) while for cost calculations the value obtained is IDR 180,390,000.00 (One Hundred and Eighty Million Three Hundred and Ninety Thousand Rupiah). Meanwhile, for the analysis of the comparative soil retaining wall for the cantilever type, the stability figures for soil bearing capacity σ max= 25.92 > 15.012 (safe), stability against sliding hazards Fgs=3.55 ≥ 1.5 (safe ), and stability against overturning hazards were obtained. SF= 6.64 > 1.5 (safe ).